2001
DOI: 10.1007/s004250100615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humidity on cuticular water permeability of isolated cuticular membranes and leaf disks

Abstract: The effects of humidity on water permeability of astomatous, isolated cuticular membranes and leaf disks of Citrus aurantium L., Vinca major L., Prunus laurocerasus L., Hedera helix L. and Forsythia intermedia (Thunb.) Vahl. were investigated by a new method using 3H2O. With isolated cuticular membranes of P. laurocerasus the isotope method resulted in values similar to those obtained by a well-established gravimetric method. Cuticular water permeability significantly increased by factors of 2 to 3 when air hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 34 publications
(37 reference statements)
4
93
0
Order By: Relevance
“…Total water loss through an inert membrane would thus vary in response to changes in the environmental humidity, with the risk of massive water loss in dry conditions. This phenomenon is typically observed in the plant cuticular film that coats the leaves (1,4), as displayed in Fig. 1.…”
mentioning
confidence: 79%
“…Total water loss through an inert membrane would thus vary in response to changes in the environmental humidity, with the risk of massive water loss in dry conditions. This phenomenon is typically observed in the plant cuticular film that coats the leaves (1,4), as displayed in Fig. 1.…”
mentioning
confidence: 79%
“…This increase in water loss during storage may be due to the artificially higher humidity environment of fruit bagged with plastic, which may therefore influence structure and/or composition of the cuticle and/or lenticels. Schreiber et al (2001) demonstrated that non-esterified, free carboxyl groups present in the cutin polymer matrix contributed to the effect of humidity on cuticular water permeability. This humidity-sensitive polar path of cuticular water permeability is arranged in parallel with the humidityindependent non-polar path formed by lipophilic wax components of the cuticle.…”
Section: Postharvest Behaviour In Rela-tion To Preharvest Factorsmentioning
confidence: 99%
“…Nevertheless, individual leaves differed both in the amounts of colonization that they supported and in A. pullulans population dynamics on microsites. This may be due to differences in cuticle erosion, which could alter topography, surface wettability, and exudation of nutrients (2,18,24), or in other inherent properties. Leaf position could also influence exposure to abiotic factors (such as UV radiation), deposition of exogenous nutrients, or photosynthesis.…”
Section: Spatial Variation In Colonization Bymentioning
confidence: 99%
“…In the field, microbes on the phylloplane are exposed to fluctuations in sunlight, moisture, temperature, and wind (9,12). The cuticle erodes, which can alter leaf topography, the wettability of the surface, exudation of nutrients, and retention of microbes (5,18,24). The microbial species composition also changes over time, and some inhabitants may influence other colonists by producing inhibitory compounds (2,13,16).…”
mentioning
confidence: 99%